TMMI Integration with Agile and Test Process - Unudulmaz, Ahmet; Kalipsiz, Oya (ASSOC COMPUTING MACHINERY, 2020)
Test Maturity Model Integration (TMMI) has a staged architecture and is a detailed model for process improvement. This model focus on test process improvements and contains five maturity levels. Applying this approach to the project has a positive impact on product quality and test effort. Besides positive impact, Test Maturity Model Integration contains heavy documentation. Applying scrum practice with this model can reduce the documentation and improve test process quality. In this case, Test Maturity Model Integration (TMMI) Level -- 2 Managed step is mapped with agile and test practices. Test Policy and Strategy, Test Planning, Test Monitoring and Control, Test Execution and Test Environment areas are discussed and they matched with not only scrum practice but also some test practices (Risk Based Testing, Use Case Testing). In the end, TMMI coverage percentage will be given and improvements areas will be defined. TMMI Level 4 metrics will be used for a development project and results will be showed. This model also can be adapted different areas, which is using agile and scrum practice.
Keywords: TMMI; Managed; Agile with TMMI; Test Policy; Test Strategy; Test Plan; Test Design; Computer Science